TRANSFORMATIONAL LEADERSHIP IN BUILDING THE PERFORMANCE OF PUBLIC ORGANIZATIONS IN THE ERA OF DISRUPTIONS; A CONCEPTUAL AND PHILOSOPHICAL ANALYSIS - Feri Agung Nugraha; Iksan Muliawan; Deni Effendi; Abdillah; Yeti Rohayati (Journal Informatic, Education and Management (JIEM), 2026)
Transformational leadership is a leadership model that focuses on organizational change through inspiration , strategic vision , and individual empowerment . In public organizations , this model is important to face the challenges of the era of disruption characterized by rapid social , political , and technological change . This study uses a literature study method to analyze the role of transformational leadership in improving the performance of public organizations . The results of the study indicate that transformational leadership is able to increase organizational effectiveness through the development of an innovative work culture , increasing employee motivation , and strengthening commitment to organizational goals and public services . Philosophically , transformational leadership is seen as a process of organizational humanization , in which leaders act as agents of change who build awareness , meaning , and moral orientation . Therefore , this leadership model is relevant to support bureaucratic reform that is more responsive , adaptive , and oriented towards the interests of society . The success of public organizations in the era of disruption does not only depend on the system and structure , but also on the quality of leadership that is able to drive meaningful change .